Entity Framework tutorial : learn to build a better data access layer with the ADO.NET Entity Framework and ADO.NET data services - Kanjilal, Joydip (Packt Pub., 2008)
Annotation This book is written as a tutorial, leading you through examples to illuminate the main theory and get you working with the Entity Framework as quickly as possible. This book is for C# developers who want an easier way to create their data access layer. You will need to be comfortable with ADO.NET, but you don't need to know anything about the Entity Framework. Along the way we will create some ASP.NET applications, so being familiar with this will also help.
Title from title screen.
Includes index.
Keywords: ActiveX.; Microsoft LINQ.; Microsoft .NET Framework.; ActiveX; Microsoft LINQ; Microsoft .NET Framework; Database design.; Query languages (Computer science); elektronické knihy; electronic books